Penerapan Model Pembelajaran Kooperatif Method Make A Macth Untuk Meningkatkan Motivasi Belajar Siswa pada Pokok Bahasan Ikatan Kimia Kelas X IPA 1 SMA Negeri 2 Singingi - Ronita Ronita; Asregi Asril; Nofri Yuhelman (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
Abstract This research aims to increase students’ motivation through cooperative learning model make a macth method using quation cards and answer cards on chemical bonding material in class X IPA 1 SMAN 2 Singingi. This type of research is research is classroom action research. Carried out in three cycles. The stages of research in each cycle include planning, action, observation and reflection. The research instrument used were observation sheets of student activities and student perception questionnaires. The subjects in this study were students of class X IPA 1 at SMAN 2 Singingi. Which numbered 27 students. From the results of the research observation sheet student’s activity in the first cycle was 55,5, in the second cycle was 77.7%, in the third cycle was 100%. Whilw for the average percentage for the questionnaire perceptions of students in the first cycle was 56,5%, in the second cycle was 66,1%, in the third cycle was 87,4%. From these results it can be concluded that learning using the method of using a question card and answer card on chemical bonding material can increase student learning motivation. Keywords: Class Action Research, Make a Macth, Chemical bond, Leraning Motivation.